Rituximab as Maintenance Treatment for Systemic Lupus Erythematosus: A Multicenter Observational Study of 147 Patients. Issue 10 (30th August 2019) - Cassia, Matthias A.; Alberici, Federico; Jones, Rachel B.; Smith, Rona M.; Casazza, Giovanni; Urban, Maria L.; Emmi, Giacomo; Moroni, Gabriella; Sinico, Renato A.; Messa, Piergiorgio; Hall, Frances; Vaglio, Augusto; et al.
Abstract : Objective: The efficacy of rituximab (RTX) in systemic lupus erythematosus (SLE) is a subject of debate. This study was undertaken to investigate the outcomes of RTX treatment in a European SLE cohort, with an emphasis on the role of RTX as a maintenance agent. Methods: All patients with SLE who were receiving RTX as induction therapy in 4 centers were included. Patients who received a single course of RTX and those who received RTX maintenance treatment (RMT) were followed up after treatment. Disease flares during the follow‐up period were defined as an increase in disease activity and the number or dose of immunosuppressive drugs. Results: Of 147 patients, 27% experienced treatment failure at 6 months. In a multivariate analysis, a low number of previous immunosuppressive therapies ( P = 0.034) and low C4 levels ( P = 0.008) reduced the risk of treatment failure. Eighty patients received RMT over a median of 24.5 months during which 85 relapses, mainly musculoskeletal, were recorded (1.06 per patient). At the time of the last RTX course, 84% of the patients were in remission. Twenty‐eight (35%) of 80 patients never experienced a flare during RMT and had low damage accrual. Active articular disease at the time of the first RTX administration was associated with a risk of flare during RMT ( P = 0.011). After RMT, relapse‐free survival was similar to that in patients receiving a single RTX course ( P = 0.72). Conclusion: RMT is a potential treatment option for patients with difficult‐to‐treat disease. Relapses occur during RMT and are more likely in those with active articular disease at the time of the first RTX administration. Relapse risk after RMT remains high and apparently comparable to that seen after a single RTX course.